Sixty Years at the Rega Institute - Erik De Clercq (Viruses, 2025)
I started my research career (in 1965) on interferon by identifying polyacrylic acid (PAA) as an interferon inducer. Poly(I).poly(C), discovered by Maurice Hilleman’s group, proved to be more potent as an interferon inducer, and through its mRNA, we were able to clone and express human β-interferon. The discovery of the reverse transcriptase (RT) by Temin and Baltimore (in 1970) brought me to the detection of suramin as a powerful RT inhibitor and enabled Sam Broder and his colleagues to identify suramin as the first inhibitor of HIV replication. In this capacity, it was subsequently superseded by AZT and other 2′,3′-dideoxynucleoside (ddN) analogs, including d4T. In collaboration with Antonín Holý, we discovered several acyclic nucleoside phosphonates as potent inhibitors of both HIV and HBV (hepatitis B virus) replication. In collaboration with Paul Janssen, we identified various non-nucleoside RT inhibitors (NNRTIs) of HIV-1 replication. Of the nucleotide RT inhibitors (NtRTTs), tenofovir emerged as the most promising congener. It was derivatized to its oral prodrugs TDF and TAF. To enhance their efficacy, they were combined with other anti-HIV drugs, and two of them were pursued (and found efficacious) in the Pre-Exposure Prophylaxis (PrEP) of HIV infections.